Analyzing EOQ Model for Imperfect Items With Time Dependent Demand Under Substitution of Two Products - Singh, Chaman; Rao Ambedkar, Gurudatt; Kohli, Jyoti; Tehri, Roopesh (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025)DO - 10.2298/YJOR230415045S, 2024)
The inventory model is based on the quantity of order and the time at which orders for particular goods are to be placed. In this paper, models with defective items have been discussed and the EOQ approach has been shown. One-way substitution of item is used in case of scarcity of the first item. The demand for the items is based on the Heaviside function. It is noticed that the presence of defective items hampers the demand of the two items differently. To establish the virtue of our model, a numerical example and sensitivity analysis is imparted.